Analisis Kinerja Simpang Lengan Empat Tak Bersinyal Jl. Wadungasri – Jl. Berbek – Jl. Gedong Masjid Kab Sidoarjo - Pratama, M Bagas; Hadi Putra, Kurnia; Sekartadji, Ratih; mca, Theresia (CV RIFAINSTITUT, 2025)
The Wadungasri, Waru four-way intersection is one of Sidoarjo Regency's intersections located within a commercial and industrial area, serving as a connector between industrial zones and an alternative route to the toll road and the airport. A review to improve its performance is necessary due to the high traffic volume, especially during peak hours. This research aims to determine the traffic performance under existing conditions and provide alternative solutions to enhance its performance. The study was conducted over three days: two working days and one holiday. The analysis is based on the PKJI (Indonesian Road Capacity Manual) 2023 guidelines, and the results are simulated using PTV Vissim student 2022. The collected data includes intersection geometry, AADT (Average Annual Daily Traffic) data, and population data. The analysis results for the intersection under existing conditions showed a Degree of Saturation (DS) value of 0.89 in the morning and 0.97 in the afternoon. This indicates that the existing condition does not meet the PKJI 2023 requirements. An alternative solution, based on this problem, was implemented by changing the intersection into a signalized intersection (APILL) with three signal phases. The results after implementing the intersection modification showed a decrease in the DS value to 0.72 in the morning and 0.77 in the afternoon. With this change, the performance complies with the PKJI 2023 standard, which requires DS < 0.85.